Rotterodamum: Romeyn de Hooghe’s Rejected Map of Rotterdam Rediscovered - van der Werff, Laurien (The Rijksmuseum Bulletin, 2021)
Having been asked by the burgomasters of Rotterdam to make a prestigious wall map of their city, the famous printmaker Romeyn de Hooghe (1645-1708) initially supplied a disappointing product that the burgomasters rejected. It was known that this had happened, but what was not known is that a unique impression of the rejected map, titled Rotterodamum, survives in the Print Room’s collection. The discovery of Rotterodamum provided the opportunity to shed more light on De Hooghe’s commission, the production process and his working methods. Rotterodamum is thus an important link in the creation of the eventual, well-known map Rotterdam met al syn gebouwen, by De Hooghe and Johannes de Vouw (c. 1660-1707).